2022
DOI: 10.1186/s12910-022-00752-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and attitudes of medical professionals on treatment of end-of-life patients in intensive care units in the Republic of Croatia: a cross-sectional study

Abstract: Background Decisions about limitations of life sustaining treatments (LST) are made for end-of-life patients in intensive care units (ICUs). The aim of this research was to explore the professional and ethical attitudes and experiences of medical professionals on treatment of end-of-life patients in ICUs in the Republic of Croatia. Methods A cross-sectional study was conducted among physicians and nurses working in surgical, medical, neurological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…After removing 1572 duplicates, 7841 unique records were obtained and screened. We reviewed 167 full-text studies, of which 33 studies were finally included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing 1572 duplicates, 7841 unique records were obtained and screened. We reviewed 167 full-text studies, of which 33 studies were finally included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
“…However, there is often a lack of agreement among physicians, patients, and families over their respective roles in EOL decision-making [4]. The involvement of nurses has also been a point of interest in various studies [5][6][7][8][9][10][11][12][13][14][15][16][17], while the views of the general public have not been comprehensively examined [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results showed that the consent rate of ICU nurses in assisting physicians in signing the decision letter was low. Multiple studies have shown that nurse involvement in the end-of-life decision-making process is widely recognized, but in practice, nurses are not included 29,30 . In the traditional Chinese medical hierarchy, physicians lead communication with patients and families about decisions, and they are major leaders of decision making, whereas nurses have a low participation rate 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that nurse involvement in the end-of-life decision-making process is widely recognized, but in practice, nurses are not included. 29,30 In the traditional Chinese medical hierarchy, physicians lead communication with patients and families about decisions, and they are major leaders of decision making, whereas nurses have a low participation rate. 31 In fact, nurses, doctors, and patients are equal and share information in shared decision making.…”
Section: Icu Nurses' Decision-making Intention For Patients At the En...mentioning
confidence: 99%
“…Before the publication of the guidelines, Croatian scientists conducted an extensive research project investigating the values and decisions in end-of-life situations. A part of the project was a study exploring the attitudes and experiences of physicians and nurses treating end-of-life patients in ICUs ( 4 ). According to the study, decisions on LST limitation were not frequently made.…”
mentioning
confidence: 99%